Avaliação de segurança e eficácia terapêutica da associação de Cassia fistula L, Cassia angustifólia Vahl, Tamarindus indica L, Coriandrum sativum L e Glycyrrhiza glabra L em pacientes com constipação intestinal - Soares, Aline Kércia Alves (2008)
Constipation is a common clinical problem that comprises a constellation of symptoms that include excessive straining, hard stools, feeling of incomplete evacuation, use of digital maneuvers, or infrequent defecation. The treatment is composed by behavioral measures and a therapeutic approach. Initial intervention should include dietary measures and fiber supplements; however, if fiber supplement action is ineffective, substances that increase the fecal bolus, lubricants, osmotic agents and laxatives can be used. The aim of the present study was to establish the efficacy, safety and validate an analytical method. Tamarine® jelly, a phytotherapic product from Barrenne Indústria Farmacêutica Ltda. a phytomedicine used as laxative. The research project with the experimental protocol and informed consent, were submitted to and approved by the Research Ethics Committee of UFC. The chromatographic profiles of Tamarine® jelly was done for confirmation of their constituents and stability analysis using high performance liquid chromatography (HPLC). The method showed the quality of the samples tested and its stability after 2 years of storage. The toxicology clinical trial consisted of an open study with 24 healthy volunteers of both sexes, with a mean age of 26.8 ±7.8 years, who orally received a daily dose of 5g Tamarine® for 28 uninterrupted days. The volunteers were included in the study only when considered healthy after clinical evaluation, physical examination and laboratory tests which preceded the study. The laboratory tests included: heamatologic, biochemical and serologic analysis. This evaluation was repeated after the first, second, third and fourth week of treatment and at post-study. The jelly was well tolerated, however, some adverse gastrointestinal events were observed. Twenty volunteers (83.3%) reported episodes of light intestinal colic followed by hyperdefecation, five (20.8%) reported diarrhea and three (12.5%) flatulence and nausea. The clinical, electrocardiographic and laboratory tests did not show evidence of toxicity in the various organs and systems evaluated. The efficacy was evaluated in 124 constipated patients selected by Rome II criteria. The investigation was designed as a controlled, parallel and opened. After the selection period, Tamarine® (TAM) or Metamucil® (MET) was administered. Patients were provided with diary sheets to record each bowel movement and associated subjective symptoms rating stool consistency, abdominal pain and flatus. The efficacy and safety analyzed after each 14 days of treatment by the information recorded on diary and a global assessment of efficacy. Volunteers continuing with their routine activities and maintaining their normal general diets even showing a low consumption of fiber and liquids. The nutritional guidelines were implemented at the end of the study not to interfere in the results. TAM increased bowel frequency after 14 and 28 days when compared with no treatment period and on 7o, 14 o, 21o and 28o days was higher the MET (p<0,001). The stool consistency was changed and became softer in both groups. The alterations improved by TAM was observed in all treatment period (p<0,001) and MET changed only on the third week (p<0,05) . The patient’s global efficacy score (p=0,01 e 0,0367) and investigator’s (p=0,0083 e 0,0193) realized that on 14º and 28º days of treatment was superior for the TAM group compared with MET. No signs of clinical or laboratory toxicity was observed throughout the treatment period. Confirming their traditional use, the administration of 5g of jelly Tamarine ® phytotherapic proved to be safe and effective in the treatment of constipation.